Schizophrenia - Castle, David J.; Buckley, Peter F. (Oxford psychiatry library., 2015)
Part of the Oxford Psychiatry Library of pocketbooks, this user-friendly and practical guide will outline the diagnosis, evaluation and treatment of patients with schizophrenia. Co-authored by two global experts on the management of patients with psychosis, this pocketbook will serve as a useful guide for psychiatrists, trainees, psychiatric specialist nurses, and interested general practitioners. Schizophrenia is one of the most disabling mental illnesses and is also highly prevalent, occurring in approximately 1% of the population and affecting both men and women equally.